2015
DOI: 10.20491/isader.2015315710
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mobbing on Burnout Syndrome at Workplace: An Application on Health Staff in Turkey

Abstract: People feel themselves inadequte, desperate and have problem of social isolation as a result of mobbing and occupational burnout in working places. Thus it threats life, health and productivity of people. Mobbing and occupational burnout are common problems in health sector. The aim of this study was to determine the levels of mobbing and occupational burnout of health staff and to reveal the influence of mobbing on occupational burnout. As the way of collecting data, a questionnaire consisting of Leymann and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“….11.02.6 eISSN: 2357//dx.doi.org/10.15405/epsbs. -1330 having an independent risk factor with high emotional exhaustion (Türkan & Kiliç, 2015). Removing mobbing and conflicts, enforcing creative works, preventing monotony, providing health work environment, avoiding stress, and protecting human psychological situation are ways of overcoming BS (Gürbüz et all., 2009).…”
Section: Hypothesis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“….11.02.6 eISSN: 2357//dx.doi.org/10.15405/epsbs. -1330 having an independent risk factor with high emotional exhaustion (Türkan & Kiliç, 2015). Removing mobbing and conflicts, enforcing creative works, preventing monotony, providing health work environment, avoiding stress, and protecting human psychological situation are ways of overcoming BS (Gürbüz et all., 2009).…”
Section: Hypothesis Resultsmentioning
confidence: 99%
“…Preventing communication, social isolation, spreading rumors, affecting occupational situation and affecting physical health of victims are types of mobbing methods. Excessive workload, insufficient wages and even increasing violence were found reasons of burnout at work place with not receiving treatment they deserve and not having satisfactory living conditions (Türkan & Kiliç, 2015). According to Social Security Institution (SGK) statistics, a worker loses his life every 10.9 hours.…”
Section: ) Desensitizationmentioning
confidence: 99%
“…On the other hand, a survey from Turkey in healthcare professionals from three different cities included workers from private hospitals, state hospitals, university hospitals, and other health centers revealed that the level of mobbing did not vary depending on gender, but on the marital status and age. Singles and younger employees were subjected to mobbing more than the married and older ones [35].…”
Section: Discussionmentioning
confidence: 99%